PENINGKATAN KAPASITAS FASILITATOR SURVEILANS VEKTOR DEMAM BERDARAH DENGUE DI KOTA SALATIGA - Aryani Pujiyanti; Riyani Setiyaningsih; Wiwik Trapsilowati; Anggi Septia Irawan; Muhammad Choirul Hidajat (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
Distribution of Dengue Hemorrhagic Fever case in Salatiga in 2011 - 2015 showed wide expansion of the case. Dinas Kesehatan Kota Salatiga in collaboration with B2P2VRP performed capacity building of vector surveillance facilitators using interactive method as an early warning system response to the spread of DHF transmission. Facilitators were cadres and teachers who were expected to optimize larval monitoring activities in family and at school. The stydy objective was to measure level of knowledge of facilitators before and after receiving capacity building activities. Research was conducted at Kelurahan Gendongan and Tingkir Tengah with data collection in February - September 2014. The research was an intervention study with one group pre-post test without control design. The result showed that capacity building could increase knowledge of both the facilitator (PSN cadres and teachers) before and after the intervention. There was no difference of post test knowledge level between cadre group and teacher. Capacity building activities with interactive methods can increase participants' knowledge with different educational background. The health office was recommended to use interactive methods in refreshing DBD vector surveillance materials on cadres and teachers to improve the sustainability of community participation in other kelurahan in larva surveys.